2010
DOI: 10.1073/pnas.1004119107
|View full text |Cite
|
Sign up to set email alerts
|

Essential genes from Arctic bacteria used to construct stable, temperature-sensitive bacterial vaccines

Abstract: All bacteria share a set of evolutionarily conserved essential genes that encode products that are required for viability. The great diversity of environments that bacteria inhabit, including environments at extreme temperatures, place adaptive pressure on essential genes. We sought to use this evolutionary diversity of essential genes to engineer bacterial pathogens to be stably temperature-sensitive, and thus useful as live vaccines. We isolated essential genes from bacteria found in the Arctic and substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Temperature-resistant variants of S3 ligA had mutations that introduced changes at the N terminus of the LigA product (Table 2), and we were surprised to find that the mutations were identical to those previously found in temperature-resistant mutants of S1 ligA (26). We noted that both of the S1 and S3 alleles had the lowest predicted RBS strengths (86 arbitrary units [AU]) of all of the alleles and wondered if the mutations leading to temperature resistance affected the strengths of the RBSs.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Temperature-resistant variants of S3 ligA had mutations that introduced changes at the N terminus of the LigA product (Table 2), and we were surprised to find that the mutations were identical to those previously found in temperature-resistant mutants of S1 ligA (26). We noted that both of the S1 and S3 alleles had the lowest predicted RBS strengths (86 arbitrary units [AU]) of all of the alleles and wondered if the mutations leading to temperature resistance affected the strengths of the RBSs.…”
Section: Resultsmentioning
confidence: 90%
“…Predictably, these cold adaptation and heat lability properties extend to essential proteins. In our previous work, we have found that psychrophilic forms of DNA ligase are inactivated in a temperature range appropriate for engineering mesophilic bacterial to temperature-sensitive (TS) forms that can be used for live vaccines (26). In this work, we have discovered new alleles of ligA conferring psychrophilic properties and show that they impart a range of TS phenotypes in bacteria.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Intracellular growth assays were performed essentially as described previously (26), using the mouse macrophage-like cell line J774. Growth of bacterial strains and temperature shifts were done as previously described (27). PT13a strains were grown in microtiter plates, and the A 595 was measured every 15 min with a BioTek EL808 plate reader.…”
Section: Methodsmentioning
confidence: 99%